Exchange rate, remittances and expenditure of foreign-born households: evidence from Australia - Syed Hasan; Nazmun Ratna; Shamim Shakur (Global Labor Organization (GLO), 2019)
We examined the impact of the depreciation of the Australian dollar (AU) during 2013-2015 on the expenditure of households with foreign-born members (HFBMs) in Australia. Employing the difference-in-differences method and 2013-2015 Nielson Homescan Panel Survey data, we found that HFBMs spent around 2.4 percent more on their food expenditure in 2014 and 4.0 percent more in 2015 compared to their native counterparts. Further investigation indicated that neither incomes nor food prices nor the expenditures on imported food items changed differently for any group in that period, while an analysis with HILDA survey data indicates a similar pattern for total expenditures. With reduced outward aggregate remittances from Australia over the same time, we argue that falling AU induces HFBMs to substitute for consumption in the home country with that in the host nation. Our empirical results provide fresh insights on how changes in the exchange rate may affect immigrants differently than natives.
Keywords: D12; D60; I30; Z13; Z18; 330; Australia; exchange rate; immigrant; consumption